Free Education and the Intergenerational Transmission of Cognitive Skills in Rural China - Zheyuan Zhang; Hui Xu; Ruilin Liu; Zhong Zhao (Institute of Labor Economics (IZA), 2024)
This paper estimates the impact of the Free Education Policy, a major education reform implemented in rural China in 2006, as a natural experiment on the intergenerational transmission of cognitive skills. The identification strategy relies on a difference-in-differences approach and exploits the fact that the reform was implemented gradually at different times across different provinces. By utilizing nationally representative data from the China Family Panel Studies, we find that an additional semester of exposure to the Free Education Policy reduces the intergenerational transmission of parent and child cognitive scores by an approximately 1% standard deviation in rural China, indicating a reduction of 3.5% in intergenerational cognitive persistence. The improvement in cognitive mobility across generations might be attributed to enhanced school attainment, the relaxation of budget constraints, and increased social contact for children whose parents are less advantaged in terms of cognitive skills.
Keywords: H52; I24; J24; 330; free education policy; intergenerational transmission; cognitive skills